Cross-sectional associations between prevalent vertebral fracture and pulmonary function. The sixth Tromso Study - Morseth, Bente; Melbye, Hasse; Waterloo, Svanhild Haugnes; Thomassen, Marte Renate; Risberg, Marijke Jongsma; Emaus, Nina (BMC Geriatrics, 2013)
Persons with vertebral fracture may have reduced pulmonary function, but this association has not been much studied. The aim of this cross-sectional study was therefore to examine the relationship between vertebral fracture and pulmonary function in a general, elderly population. Vertebral morphometry was used for vertebral fracture assessment in 2132 elderly men (n = 892) and women (n = 1240) aged 55 to 87 years in the population-based Tromsø Study 2007–08. Pulmonary function was examined by spirometry. Pulmonary function was expressed as FVC% predicted, FEV1% predicted, and FEV1/FVC% predicted values, adjusted FVC, FEV1, and FEV1/FVC, and obstructive and restrictive ventilatory impairment. Vertebral fracture was classified according to appearance, number, severity, and location of fractures. Associations were analyzed using general linear and logistic models. FVC% predicted and FEV1% predicted values were not associated with vertebral fracture (P > 0.05), whereas FEV1/FVC% predicted ratio was associated with both prevalent fracture, number of fractures, severity of fractures, and fracture site in men (P < 0.05), but not in women. When FVC, FEV1, and FEV1/FVC values were adjusted for multiple covariates, we found no significant association with vertebral fracture. Obstructive and restrictive ventilatory impairment was not associated with prevalent vertebral fracture. In conclusion, this study did not confirm any clinically relevant associations between prevalent vertebral fracture and ventilatory impairment in elderly individuals.